O-GlcNAcylation-induced GSK-3β activation deteriorates pressure overload-induced heart failure via lack of compensatory cardiac hypertrophy in mice - Matsuno, Mahito; Yokoe, Shunichi; Nagatsuka, Takehiro; Morihara, Hirofumi; Moriwaki, Kazumasa; Asahi, Michio (Frontiers in Endocrinology, 2023)
O-GlcNAc transferase (OGT) modulates many functions of proteins via O-GlcNAcylation that adds O-linked β-N-acetylglucosamine (O-GlcNAc) to the serine/threonine residues of proteins. However, the role of O-GlcNAcylation in cardiac remodeling and function is not fully understood. To examine the effect of O-GlcNAcylation on pressure overload-induced cardiac hypertrophy and subsequent heart failure, transverse aortic constriction (TAC) surgery was performed in wild type (WT) and Ogt transgenic (Ogt-Tg) mice. Four weeks after TAC (TAC4W), the heart function of Ogt-Tg mice was significantly lower than that of WT mice (reduced fractional shortening and increased ANP levels). The myocardium of left ventricle (LV) in Ogt-Tg mice became much thinner than that in WT mice. Moreover, compared to the heart tissues of WT mice, O-GlcNAcylation of GSK-3β at Ser9 was increased and phosphorylation of GSK-3β at Ser9 was reduced in the heart tissues of Ogt-Tg mice, resulting in its activation and subsequent inactivation of nuclear factor of activated T cell (NFAT) activity. Finally, the thinned LV wall and reduced cardiac function induced by TAC4W in Ogt-Tg mice was reversed by the treatment of a GSK-3β inhibitor, TDZD-8. These results imply that augmented O-GlcNAcylation exacerbates pressure overload-induced heart failure due to a lack of compensatory cardiac hypertrophy via O-GlcNAcylation of GSK-3β, which deprives the phosphorylation site of GSK-3β to constantly inactivate NFAT activity to prevent cardiac hypertrophy. Our findings may provide a new therapeutic strategy for cardiac hypertrophy and subsequent heart failure.